2023
DOI: 10.1186/s12885-022-10319-7
|View full text |Cite
|
Sign up to set email alerts
|

The potential of PARP as a therapeutic target across pediatric solid malignancies

Abstract: Background Pediatric cancer is the leading cause of disease-related death in children and the need for better therapeutic options remains urgent. Due to the limited number of patients, target and drug development for pediatrics is often supplemented by data from studies focused on adult cancers. Recent evidence shows that pediatric cancers possess different vulnerabilities that should be explored independently from adult cancers. Methods Using the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Fam et al demonstrated the single-agent activity of both TDP1 and PARP inhibition in RMS cell lines as well as the combined efficacy of either TDP1 or PARP inhibition with irinotecan analogues [139]. In another preclinical study, the PARP inhibitor talazoparib was found to be the most effective when combined with SN-38, the active metabolite of irinotecan, in RMS cell lines [142]. Additional preclinical work demonstrated that the Wee1 inhibitor AZD1775, alone and in combination with irinotecan or vincristine, led to G2/M phase arrest, increased DNA damage, and had anti-tumor activity against in vivo models of high-risk RMS [138,143].…”
Section: Rhabdomyosarcomamentioning
confidence: 99%
“…Fam et al demonstrated the single-agent activity of both TDP1 and PARP inhibition in RMS cell lines as well as the combined efficacy of either TDP1 or PARP inhibition with irinotecan analogues [139]. In another preclinical study, the PARP inhibitor talazoparib was found to be the most effective when combined with SN-38, the active metabolite of irinotecan, in RMS cell lines [142]. Additional preclinical work demonstrated that the Wee1 inhibitor AZD1775, alone and in combination with irinotecan or vincristine, led to G2/M phase arrest, increased DNA damage, and had anti-tumor activity against in vivo models of high-risk RMS [138,143].…”
Section: Rhabdomyosarcomamentioning
confidence: 99%
“…Despite dismal treatment responses upon single agent use, recent investigations in pediatric solid tumors provide information on beneficial effects of PARP inhibitors combined with conventional chemotherapy, ie, alkylating agents or topoisomerase inhibitors. 116 …”
Section: Potential Targeted Therapeutic Approaches To Atrtmentioning
confidence: 99%